Betaine Aldehyde Dehydrogenase (BADH) vs. Flavodoxin (Fld): Two Important Genes for Enhancing Plants Stress Tolerance and Productivity - Niazian, Mohsen; Sadat-Noori, Seyed Ahmad; Tohidfar, Masoud; Mortazavian, Seyed Mohammad Mahdi; Sabbatini, Paolo (Frontiers in Plant Science, 2021)
Abiotic stresses, mainly salinity and drought, are the most important environmental hazards that threaten worldwide food security through affecting plant growth and productivity. Plants mitigate the adverse effects of these stresses through applying different morpho-physio-biochemical mechanisms. Accumulating effective osmoprotectants, such as proilne and glycine betaine (GB), is one of the important plants stress tolerance strategies. These osmolytes can enhance plants stress tolerance by array of mechanisms including stress signal transduction, activating resistance genes, increasing levels of enzymatic and non-enzymatic antioxidant, protecting cell osmotic pressure, enhancing cell membrane integrity as well as protecting photosynthetic apparatus, especially photosystem II (PSII) complex. Genetic engineering, as one of the most important plant biotechnology methods, helps the fast development of stress-tolerant plants through the delivery of key tolerance genes involved the biosynthetic pathways of osmolytes. Betaine aldehyde dehydrogenase (BADH) is one of the important genes involved in biosynthetic pathway of GB and its introduction led to increased tolerance to variety of abiotic stresses in different plant species. Substitution of down-regulated ferredoxin at the acceptor side of photosystem I (PSI) with its isofunctional counterpart electron carrier (flavodoxin) is another applicable strategy to strengthen photosynthetic apparatus of plants under stressful condition. Heterologous expression of microbially-sourced flavodoxin (Fld) in higher plants compensates for deficiency of ferredoxin expression and enhanced their stress tolerance. BADH and Fld are multifunctional transgenes that increase stress tolerance of different plants species and maintain their production under stressful situation by protecting and enhancing photosynthetic apparatus. In addition to increasing stresses tolerance, recent studies have shown that both BADH and Fld genes can improve productivity, symbiotic performance as well as longevity of plants. Comparative analysis of these two genes in ajowan medicinal plant showed the superiority of the BADH over the Fld in enhancing drought and salinity stresses tolerance. Because of multigenic and complex nature of abiotic stresses, the concomitant delivery of BADH and Fld transgenes can lead to more satisfying results in desired plants, as these two genes enhance plants stress tolerance through different mechanisms and their cumulative effect can be much more beneficial than their individual effect.